Eksplorasi Nilai Pendidikan Islam: Kajian Komparatif Hadis Tarbawi antara Masa Rasulullah dan Era Saat Ini - Rahardja, Muhammad Nurfaizi Arya; Ibrohim, Muhammad Maulana Malik; Akmal, Miftahul Jannah; Putri, Annisa Ningtias Cevie; Sumarna, Elan (UIN Syarif Hidayatullah Jakarta, 2023)
This study aims to analyse and reveal the best education during the time of the Prophet, as mentioned in Muslim hadith No. 6425. The qualitative research method is used in this study, and library research is used to obtain research data. The research data were analysed using the descriptive-analysis method and the tahlili hadith method to analyse the hadith. The results in this study are (1) Muslim hadith No. 6425 is worth ṡaḥīḥ li żātihi, and its sanad is muttaṣil, (2) Education during the Prophet's era is divided into two periods, namely the Mecca and Medina periods, (3) In Mecca, the Prophet's education material focused on aqidah education, worship, morals, aqliyyah, ilmiyyah, and health. While in Medina, the Prophet's education focused on social and political affairs, and (4) The method of education in the Prophet was carried out with several educational methods, namely lectures, discussions, advising, practical experiments, questions and answers, and praise